Analysis of postmortem changes in internal organs and gases using computed tomography data. (March 2017) - Okumura, Miki; Usumoto, Yosuke; Tsuji, Akiko; Kudo, Keiko; Ikeda, Noriaki
Highlights: We investigated postmortem changes using CT data. We analyzed relationships between PMI and lung volume, intrahepatic gas, and intrarectal gas. Intrarectal gas decreased with postmortem changes, while intrahepatic gas increased. We constructed an equation for estimation of PMI. Our data may provide a useful index of postmortem changes for estimation of PMI. Abstract: Postmortem computed tomography (PMCT) is a useful method to identify various causes of death and measure the volume of internal organs and gases. The purpose of this study was to investigate postmortem changes as measured by PMCT, and the relationship between the volume of organs and gases and postmortem interval (PMI). Forty-six cadavers (22 men, 24 women) were examined by CT before autopsy. The volumes of the lungs, intrahepatic gas, and intrarectal gas were measured by CT using a workstation. A stepwise regression analysis was used to establish a predictive equation to ascertain the measured volume using factors including sex, age, height, body mass index (BMI), body surface area (BSA), and PMI. For estimation of PMI, stepwise regression analysis was used. In the equations for each measured volume, height, diaphragmatic height, and BSA were adopted for the left lung; height and diaphragmatic height were adopted for the right lung; PMI was adopted for intrahepatic gas; and sex and PMI were adopted for intrarectal gas. In the PMI equations, left lung volume, intrahepatic gas, and intrarectal gas were adopted together with sex, weight, and BMI. Values of intrahepatic gas decreased with postmortem changes, while intrarectal gas increased. This may be useful in investigation of postmortem changes. It will be necessary to include other parts of the intestine and to analyze volume changes in gases from these parts after death.